2019
DOI: 10.4025/actascianimsci.v42i1.45517
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vegetable oils inclusion on the performance, hormonal levels and hsp 70 gene expression in broilers under heat stress

Abstract: The aim of the present study was to compare the effects of unsaturated and saturated oils on the performance, hormonal levels and hsp gene expression in broiler chickens exposed to heat stress. 300 one-day male broiler chicks were assigned to 4 treatments (Diets containing palm, corn, linseed or olive oils) with 5 replicates. At day 28 of age, 2 chickens were removed from each replicate, then blood samples and liver tissue samples were collected for analyses. Feeding linseed and olive oil reduced feed conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to Mujahid et al [45], the addition of 6.7% olive oil to the diet of broiler chickens reared under thermo-neutral or heat-stress conditions reduced mitochondrial ROS production and decreased oxidative damage in the birds. Recent feedings trials performed in broilers reared at high ambient temperatures revealed the antioxidant effect of olive oil and the improvement of the birds' immune system [46], the improvement of hormonal indicators and chickens' performances as well as the increased activity of heat tolerance genes in chickens [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Mujahid et al [45], the addition of 6.7% olive oil to the diet of broiler chickens reared under thermo-neutral or heat-stress conditions reduced mitochondrial ROS production and decreased oxidative damage in the birds. Recent feedings trials performed in broilers reared at high ambient temperatures revealed the antioxidant effect of olive oil and the improvement of the birds' immune system [46], the improvement of hormonal indicators and chickens' performances as well as the increased activity of heat tolerance genes in chickens [47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the review of the literature shows that there are currently no data available on the dietary impact of OP on the thermal comfort of broilers. In contrast, there are a few studies on the nutritional effects of various by-products such as olive oil [45][46][47] and olive leaves [48,49] on heat stress in chickens. Recent nutritional studies in broilers reared at high ambient temperatures have demonstrated the antioxidant effect of olive oil [45,46], improved birds' immune system [46], improved hormonal indicators and chick performance and the increased activity of genes responsible for the birds' thermal resistance [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few genes involved in lipid metabolism [acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS)] had an upregulated expression in the serum of laying hens fed with a diet supplemented with olive cake (118). Furthermore, olive oil increased the expression of many genes encoding for heat shock proteins in broiler chickens, improving their tolerance to heat stress (119).…”
Section: Effects On Gene Transcriptionmentioning
confidence: 99%